MARIE-LAURE’S STRUGGLE AS BLIND TEENAGER IN ANTHONY DOERR’S ALL THE LIGHT WE CANNOT SEE - Herdianti, S.S, Monica (Faculty of Letters, Dr. Soetomo University, 2020)
Herdianti, M. (2020). Marie-Laure's Struggle as Blind Teenager in Anthony Doerr's All The Light We Cannot See. UIN Sunan Ampel Surabaya. Keywords: characterization, struggle, invasion. This article aims to discuss Marie-Laure characterization and her struggle to fulfill her needs based on Maslow’s hierarchy of needs theory in the novel All The Light We Cannot See novel . The study's focus is on Marie-Laure and her struggle for her life in a precarious situation when the German invade her hometown. Qualitative design is choosen as the method of study. New criticism (character and characterization) and the hierarchy of needs according to Abraham Maslow, are selected as the theory for analysis. The results: first, Marie's personality in the novel is intelligent, brave, and inquisitive. Second, Marie's struggle in the first level is to stay alive without her vision in a precarious situation, in the second level is to escape to find a safety place, in the third level is learn her new environment and get to know her new neighborhood, in the fourth level is Marie’s interested in science make her life back. Marie's struggle in the last level is to pass all the problems and became a mollusk expert. The third results shows the support from her father (Daniel Le-Blanc), her great-uncle (Etienne), and Madam Manec (Etienne house keeper).